Potensi Riba dan Gharar dalam Arisan Online: Telaah Fiqih Muamalah Moderen - Habibah, Nur; Fadhilatul Azizah; Anggi Silviani; Alam Tarlam (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This study examines the potential elements of riba (usury) and gharar (uncertainty) in the practice of online rotating savings (arisan) from the perspective of contemporary Islamic jurisprudence (fiqh muamalah). With the advancement of digital technology, traditional social arisan has evolved into an online financial platform offering convenience and speed. However, this transformation also raises concerns about the presence of prohibited elements in Islamic law. This article analyzes the characteristics of online arisan, identifies the loopholes that may lead to riba, such as unclear administrative fees and auction-based disbursements, and explores aspects of gharar arising from lack of transparency, uncertain payout timing, and risk of default. Using a descriptive qualitative approach and content analysis of various popular online arisan models, the study aims to provide a comprehensive understanding of the Sharia implications. The findings are expected to serve as a reference for both practitioners and participants to ensure compliance with Islamic commercial principles, as well as to contribute to the development of a more Sharia-compliant arisan model.